Enterocin: promising biopreservative produced by enterococcus sp. - Melisa Elsie Kasimin; Suriyani Shamsuddin; Arnold Marshall Molujin; Mohd Khalizan Sabullah; Jualang Azlan Gansau; Roslina Jawan (MDPI, 2022)
Food preservation is a method used to handle and treat food products to slow down food spoilage and subsequently reduce the risk of foodborne illness. Nowadays, the demand for natural preservatives over chemical preservatives in food is increasing due to the awareness of consuming healthy food products without the risk of harmful side effects. Thus, the research and development of preservation techniques, referred to as biopreservation, is growing rapidly. In biopreservation methods, microorganisms that are known as lactic acid bacteria (LAB) and their antimicrobial substances are used to extend shelf life and maintain the nutritional value of foods. Among the most studied LAB are from the genus Enterococcus, which produces a bacteriocin called enterocin. Bacteriocins are ribosomal-synthesized antimicrobial peptides that are capable of inhibiting the growth of pathogenic bacteria that cause spoilage in food. LAB is generally regarded as safe (GRAS) for human consumption. The current application of LAB, notably Enterococcus sp. in the biopreservation of meat and meat-based products was highlighted in this review. This report also includes information on the effects of enzymes, temperature, and pH on the stability of bacteriocin produced by Enterococcus sp. An extensive compilation of numerous industry procedures for preserving meat has also been emphasized, highlighting the benefits and drawbacks of each method.